KOEFISIEN AIR LARIAN BERDASARKAN PENUTUPAN VEGETASI DAN PENGUKURAN DEBIT ALIRAN SUNGAI CEKUNGAN PENGALIRAN SUNGAI (CPS) CITARIK HULU - Haryanto, Edi Tri (Bulletin of Scientific Contribution, 2014)
Upper Citarik Catchment has an area of about 30,41 Km2 or around 30.000 Ha. Based on topographic map “Rupa Bumi Indonesia”(RBI), the upper area of the catchments still covered by forests which can restrain the increase of runoff coefficient.There is also water fall “Curug Cinulang in the Catchment, the interesting natural tourist attractions that push the growth of economic activities and tourism facilities, changing land use which can increase runoff coefficient and improve flow discarge. The research method used was land use mapping based on the Topographic Map “RBI” with scale of 1 to 25000, and measurements of each land use types using GIS techniques. Discharge estimation using empirical formula and measurements in the field. The results showed dense forest cover, plantations, and scrub affect the coefficient runoff. Forests affect the stability of the river flow based on measurements and calculations with different assumptions rainfall intensity. The river discharge was relatively stable at stations 6 and 7 with more than 90% of land covered by good forest.